Novel bilayer electrospun poly(caprolactone)/ silk fibroin/ strontium carbonate fibrous nanocomposite membrane for guided bone regeneration. Issue 16 (12th November 2020) - Etemadi, Niloofar; Mehdikhani, Mehdi; Poorazizi, Elahe; Rafienia, Mohammad
Abstract: In this study, a thin layer with a thickness of about 120 μm of poly(caprolactone) (PCL) was fabricated by electrospinning method. Then, a fibrous nanocomposite composed of PCL/silk fibroin/strontium carbonate (PCL/SF/SrCO3 ) was electrospun on the prepared layer. Then, they were characterized. The mechanical properties, water uptake, degradation rate, wettability, porosity, and bioactivity of the electrospun membrane were scrutinized in vitro. Cytotoxicity of the samples was assessed by using osteoblast‐like cells (SAOS‐2) and L929 fibroblasts. Moreover, the cell adhesion, alkaline phosphatase (ALP) activity, and calcium deposition through alizarin red staining were conducted. Results revealed that the bilayer structure doubled the optimum mechanical properties and the addition of SrCO3 up to 15%–20% increased ALP activity, calcium deposition, and bioactivity. According to the results, the nanofibrous bilayer membrane containing 20 wt% SrCO3, 20 wt% SF, and 60 wt% PCL was chosen as the optimum sample. Therefore, this membrane could be applied in guided bone regeneration (GBR). Abstract : The bilayer membrane composed of natural and synthetic biodegradable nanofibrous polymers containing strontium carbonate with suitable physicochemical, mechanical, and biological properties.